Different antithrombotic strategies to prevent cardiovascular complications in Kawasaki patients: a systematic review and meta-analysis - Ramin Assempoor; Alireza Sattari Abroy; Alireza Azarboo; Amirhossein Ghaseminejad-Raeini; Kimia Najafi; Kaveh Hosseini (BMC, 2024)
Abstract Background Coronary artery aneurysm (CAA) poses significant cardiovascular risks, particularly in Kawasaki disease (KD) patients. This systematic review and meta-analysis aim to evaluate and compare antithrombotic strategies in preventing CAA formation secondary to Kawasaki disease and the ensuing CAA cardiovascular complications. Methods Following PRISMA guidelines, we systematically searched major databases, namely PubMed, Scopus, Web of Science, and Embase. Major adverse cardiovascular events (MACE), myocardial infarction (MI), stenosis, bleeding, occlusion, and coronary artery lesion (CAL) formation were primary outcomes. Consolidated Standards of Reporting Trials (CONSORT) and Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) scores assessed study quality. A meta-analysis, as well as sensitivity analysis and meta-regression, was performed to compare the efficacy of pharmacological strategies on the outcomes. Results The study included 21 studies with 1045 patients for CAA complications and 41536 patients for CAA formation prevention. In children with CAA secondary to Kawasaki disease, the addition of warfarin to aspirin was associated with a significantly lower odds of myocardial infarction (OR = 0.26, 95% CI: 0.11-0.60, I2 = 25%) and mortality (OR = 0.18, 95% CI: 0.04-0.88, I2 = 0%) compared to aspirin alone. However, there was no significant difference in MACE (OR = 0.38, 95% CI: 0.08-1.93, I2 = 60%) and occlusion (OR = 0.17, 95% CI: 0.02-1.92, I2 = 58%). Sensitivity analysis showed reduced thrombosis (OR = 0.29, 95% CI: 0.14-0.62, I2 = 0%), MACE (OR [95% CI] = 0.22[0.06-0.84], I2 = 46%), and occlusion (OR [95% CI] = 0.08[0.02-0.44], I2 = 36%). Meta-regression did not yield significant results. Conclusions As for the acute phase of KD, no benefit was conferred from adding high-dose aspirin to the routine IVIG alone regimen. However, the complexity of outcomes and the diversity in antithrombotic interventions underscore the need for tailored approaches and further research.